Parasite assemblages of whitemouth croaker, Micropogonias furnieri: comparison between marine and brackish waters from the Argentine Sea - Alarcos, Ana Julia (2021)
The whitemouth croaker, Micropogonias furnieri, a coastal demersal fish with wide distribution in the Southwest Atlantic Ocean, is a euryhaline species, inhabiting waters with a wide range in salinity. Here, the composition of parasite assemblages of M. furnieri caught along the coastal area off Mar del Plata, Argentina, was described and the infracommunity structure compared with fish from brackish waters to determine variations of its parasite communities due to fish migration between these environments. The relationships between the presence of parasites and the diet and ecological traits of this fish host were discussed. A total of 61 fish from Mar del Plata (MDP) were examined for parasites and compared with previously published data for whitemouth croakers from Mar Chiquita coastal lagoon (MCH), an estuarine system connected to the sea. Corynosoma australe, Dichelyne sciaenidicola, and Neopterinotrematoides avaginata were the most prevalent and abundant species in MDP. Comparisons of infracommunity descriptors showed that fish from MDP harbored a higher number of parasites, as well as richer and more diverse infracommunities than those of MCH. Significant differences occurred in the structure and composition of parasite assemblages of whitemouth croaker from MDP compared to those from MCH, in which Neomacrovalvitrema argentinensis, N. avaginata, Neobrachiella chevreuxii, D. sciaenidicola, and C. australe were the key discriminating species related to these differences. The present study provides comparative data, of great importance for the understanding of parasite-host-environment interactions, particularly in a host that alternates between brackish and marine waters during its life cycle.